1979
DOI: 10.1007/bf00455238
|View full text |Cite
|
Sign up to set email alerts
|

Auditory function in guinea pigs treated with netilmicin and other aminoglycoside antibiotics

Abstract: The following aminoglycoside antibiotics netilmicin, sisomicin, gentamicin, and kanamycin were submitted to a comparative study of their ototoxicity using both reflexological (Preyer's pinnareflex) and electrophysiological (near and far field) methods. The daily s.c. administration of sisomicin, gentamicin, and kanamycin for 21 days provoked a dose-related impairment of the cochlear function, detected with all the employed techniques. On the other hand, a very low ototoxic effect of netilmicin was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The present study demonstrated that the vestibular and cochlear reflexes and electrophysiologic responses in guinea pigs dosed with netilmicin at 150 mg/kg/day for 21 days, were similar to those of saline-injected. These results confirm previous observations on the safety of netilmicin on the inner ear of guinea pigs (Brummett et al 1978;Arpini et al 1979;Bamonte et al 1980;Wersall 1980), cats (Weinberg et al 1981), monkeys (Igarashi et al 198 1) dogs and rats (Igarashi & Jensen 1981).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study demonstrated that the vestibular and cochlear reflexes and electrophysiologic responses in guinea pigs dosed with netilmicin at 150 mg/kg/day for 21 days, were similar to those of saline-injected. These results confirm previous observations on the safety of netilmicin on the inner ear of guinea pigs (Brummett et al 1978;Arpini et al 1979;Bamonte et al 1980;Wersall 1980), cats (Weinberg et al 1981), monkeys (Igarashi et al 198 1) dogs and rats (Igarashi & Jensen 1981).…”
Section: Discussionsupporting
confidence: 91%
“…1980) and less ototoxic (Brummett et a/. 1978;Arpini et a/. 1979;Bamonte et al 1980;Wersall 1980) than the other currently available aminoglycosides.…”
mentioning
confidence: 99%
“…The disposition half-lives (t11n) in plasma of the three antibiotics were comparable and within the following ranges: tl/,2a of 0.09 to 0.16 h; tl2p of 0.88 to 1.01 h; and t1/2y of 7.87 to 8.29 h. The volume of distribution in the central compartment and the total body clearance of netilmicin (294 mI/kg, 5.74 ml/min per kg) were greater than those of gentamicin (160 ml/kg, 3.40 m/min per kg) and tobramycin (204 ml/kg, 4.63 ml/min per kg). Pharmacokinetic analysis of the perilymph drug concentration-time data indicated that all three antibiotics penetrated the perilymph readily, but netilmicin cleared from the perilymph compartment faster than gentamicin and tobramycin.…”
mentioning
confidence: 85%
“…It has been reported that the aminoglycoside antibiotics that are widely used in clinical practice, such as gentamicin, tobramycin, and amikacin, show similar perilymph drug concentrations (5) and provoke substantially overlapping ototoxic reactions (1,3,5,9). Studies on neomycin, streptomycin, dihydrostreptomycin, and kanamycin (8,11) also have shown that the relative ability of each aminoglycoside antibiotic to reach greater perilymph concentration was directly related to the extent of their ototoxic damage in guinea pigs.…”
mentioning
confidence: 99%
“…The morphological changes and electrophysiological dysfunctions induced by different aminoglycosides have been extensively studied, and it is clearly established that the pattern of toxicity varies greatly within this family of antibiotics (1,8,12). For example, gentamicin affects the cochlear and vestibular systems to nearly the same extent, while amikacin preferentially damages the cochlea; netilmicin is significantly less toxic than either gentamicin or amikacin to both parts of the labyrinth (2,5,7). It has been postulated that this differential damage is related to the concentration of aminoglycoside achieved in the perilymph, i.e., the more toxic a drug, the higher its level in this inner-ear fluid (7,20), although exceptions from this pattern had been noted (6,15).…”
mentioning
confidence: 99%